Enhancement of Iraqi Light Naphtha Octane Number Using Pt Supported HMOR Zeolite Catalyst - Atiya, Mohammed A.; Rahman, Ameel Mohammed; Al-Hassani, Maha H. (Al-Khwarizmi Engineering Journal, 2013)
The hydroconversion of Iraqi light straight run naphtha was studied on zeolite catalyst. 0.3wt.%Pt/HMOR catalyst was prepared locally and used in the present work. The hydroconversion performed on a continuous fixed-bed laboratory reaction unit. Experiments were performed in the temperature range of 200 to 350°C, pressure range of 3 to 15 bars, LHSV range of 0.5-2.5h-1, and the hydrogen to naphtha ratio of 300.The results show that the hydroconversion of Iraqi light straight naphtha increases with increase in reaction temperature and decreases with increase in LHSV.High octane number isomers were formed at low temperature of 240°C. The selectivity of hydroisomerization improved by increasing reaction pressure up to 15 bars. Catalyst activity almost stable and independent of time on stream at 15 bar up to 20 h.